2014
DOI: 10.3354/ab00550
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of municipal sewage on symbiosis between mangrove plants and arbuscular mycorrhizal fungi

Abstract: The impact of municipal sewage discharge on the symbiosis between arbuscular mycorrhizal fungi (AMF) and mangrove plants in different sections along 2 constructed mangrove belts was evaluated. Each section was 33 m long and 3 m wide and planted with Kandelia obovata or Aegiceras corniculatum, the 2 most common mangrove plants in South China. A greenhouse experiment comparing the colonization intensity of AMF among different mangrove plant species under wastewater treatment was also conducted. Typical arbuscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…The presence of AMF in wetland ecosystems has received increased attention in recent years (7,9,32,33), but only a few field studies documenting AMF colonization have been conducted in paddy wetlands (2). In agreement with Watanarojanaporn et al (13), who reported that AMF are commonly present in rice roots from conventional paddy wetlands in Thailand, we found that AMF colonization in rice roots is commonly present at the heading and ripening stages though absent or rare at the early growth stages.…”
Section: Discussionsupporting
confidence: 79%
“…The presence of AMF in wetland ecosystems has received increased attention in recent years (7,9,32,33), but only a few field studies documenting AMF colonization have been conducted in paddy wetlands (2). In agreement with Watanarojanaporn et al (13), who reported that AMF are commonly present in rice roots from conventional paddy wetlands in Thailand, we found that AMF colonization in rice roots is commonly present at the heading and ripening stages though absent or rare at the early growth stages.…”
Section: Discussionsupporting
confidence: 79%
“…According to Carvalho et al [2], high levels of salinity negatively affect AMF establishment inside roots. Moreover, Wang et al [38] also reported that the intensity of AMF colonization in two mangrove species was highly dependent on the concentration of nutrients present in a municipal effluent, since high levels of N, P, and organic matter decreased AMF colonization. The observed changes in the composition and diversity of AMF's communities can be related to fluctuations in the wastewater organic load in the CW throughout different seasons/years.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, Glomus mosseae exhibited highest frequency at all inundation types; Glomus fistulosum, Sclerocystis coremioides and Glomus mosseae showed highest relative abundance at sites inundated by usual springtides, summer springtides and diurnal tides, respectively. Similarly, Wang et al (2010;2014) studied AM fungal association with two mangrove swamps in south China and found AM fungi in the form of hyphae which were commonly associated with all the mangrove species and six AM fungal species belonging to two genera viz., Glomus and Acaulospora were identified by them.…”
Section: Am Fungal Spore Populationmentioning
confidence: 99%